(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article explains the linguo-cultural, comparative, cognitive and applied linguocultural studies issues characteristic to the fairy tale genre of English and Uzbek folklore. Also, the importance of the linguistic approach to language analysis is emphasized. Language and culture, interdependence of culture, problems of communication and interaction are cultural phenomena and Since linguistic and cultural analysis is a contemporary multidisciplinary field, it makes sense that it plays a significant role in research